The effects of crime and armed conflict on provincial fiscal revenue performance - Querijero, Jullia Ryanne L.; Tagle, Ian Lincoln S.; Capuno, Joseph J. (Quezon City School of Economics, University of the Philippines Diliman, 2020)
The humanitarian costs of crime and armed conflict are indisputable. However, there has been much clamor with how these disturbances to peace and order deter the government from performing their role in the development of the Philippines. In this study, we used simple ordinary least squares, panel-data fixed effects, and panel-data random effects models in estimating the effects of crime and armed conflict on a primary indicator of state capacity, fiscal revenue performance. Results indicate that controlling for other explanatory variables, both crime and armed conflict have negative but small effects on fiscal revenue performance in the Philippines.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Fiscal sustainability -- Philippines; Firearms and crime -- Philippines